2023
DOI: 10.3389/fimmu.2022.1053457
|View full text |Cite
|
Sign up to set email alerts
|

CCL2: An important cytokine in normal and pathological pregnancies: A review

Abstract: C-C motif ligand 2 (CCL2), also known as monocytic chemotactic protein 1 (MCP-1), is an integral chemotactic factor which recruits macrophages for the immune response. Together with its receptors (e.g., CCR2, ACKR1, and ACKR2), they exert noticeable influences on various diseases of different systems. At the maternal-fetal interface, CCL2 is detected to be expressed in trophoblasts, decidual tissue, the myometrium, and others. Meanwhile, existing reports have determined a series of physiological regulators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 155 publications
0
17
0
Order By: Relevance
“…Among them, CCL2 was reported to be expressed in trophoblasts and decidual tissue at the maternal-fetal interface and proposed to contribute to immune cell recruitment, tissue remodeling, and angiogenesis during placentation. 29 On the other hand, it was also revealed that the spheroid-derived Swan71 cells increased the expressions of C-X-C motif chemokines, CXCL1, CXCL2, CXCL5, CXCL6, CXCL8, and CXCL10. A recent study indicated that CXCL1 is necessary for decidual angiogenesis during the first trimester.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among them, CCL2 was reported to be expressed in trophoblasts and decidual tissue at the maternal-fetal interface and proposed to contribute to immune cell recruitment, tissue remodeling, and angiogenesis during placentation. 29 On the other hand, it was also revealed that the spheroid-derived Swan71 cells increased the expressions of C-X-C motif chemokines, CXCL1, CXCL2, CXCL5, CXCL6, CXCL8, and CXCL10. A recent study indicated that CXCL1 is necessary for decidual angiogenesis during the first trimester.…”
Section: Discussionmentioning
confidence: 97%
“…This study showed that the expressions of C‐C motif chemokines, CCL2, CCL7, and CCL20, were increased in the spheroid‐derived Swan71 cells. Among them, CCL2 was reported to be expressed in trophoblasts and decidual tissue at the maternal‐fetal interface and proposed to contribute to immune cell recruitment, tissue remodeling, and angiogenesis during placentation 29 . On the other hand, it was also revealed that the spheroid‐derived Swan71 cells increased the expressions of C‐X‐C motif chemokines, CXCL1, CXCL2, CXCL5, CXCL6, CXCL8, and CXCL10.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we also found that other inflammatory factors such as MCP‐1, also known as CCL2, increased in spleen lysate, BM lysate and serum at day 1. Since CCL2 is an integral chemotactic factor known to play a crucial role in recruiting monocytes from the bone marrow to various tissues including the spleen, in response to inflammation or injury (Lin et al , 2022), it may also recruit the myeloid cells to the inflammation site during acute phase post A. m . stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we also found that other inflammatory factors such as MCP-1, also known as CCL2, increased in spleen lysate, BM lysate and serum at day 1. Since CCL2 is an integral chemotactic factor known to play a crucial role in recruiting monocytes from the bone marrow to various tissues including the spleen, in response to inflammation or injury (Lin et al, 2022), it may also recruit the myeloid cells to the inflammation site during acute phase post A. m. stimulation. We found that late-onset delayed EMH in the spleen is mediated by innate immune signals, particularly TLR2/4 and IL-1R, with the latter possibly being regulated by local and persistent secretion of IL-1a upon A. m. stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the compound was not able to reduce the secretion of TNF-α, an important cytokine involved in triggering the innate immune response against host invaders [27,28]. The inhibited cytokines are responsible for different biological effects, contributing to the development and progression of inflammatory responses and increasing the response of cells involved in the immune system [29][30][31][32]. Similarly, other studies have already shown the ability of different 1,4-DHP derivatives to inhibit the production of these same pro-inflammatory cytokines in different experimental models, and as in our experiments, the 1,4-DHP derivatives did not reduce TNF-α levels [10,11,33].…”
Section: Groupmentioning
confidence: 97%